Glucosamine Sulfate: a Structure Modifying Drug for Osteoarthritis - Wattanapitayakul, Suvara K.; Phomchirasilp, Srichan (Journal of Basic and Applied Pharmacology, 2015)
Osteroarthritis (OA) is a degenerative disease of the articular cartilage, leading to a full-thickness loss of joint surface. Other joint tissues also contribute to the pathogenesis of OA.There are two major goals of OA therapy: 1) to alleviate the symptoms (symptom modification) and 2) to control the progression of the disease (structure modification). Although non-steroidal antiinflammatory drugs have been widely used to control OA symptoms, their effects on the progression of OA are uncertain. Therefore, a new class of therapeutic agents that possesses long-term disease-modifying activity has been introduced, such as glucosamine sulfate (GS) and chondroitin. GS is a salt of natural occurring amino-monosaccharide glucosamine. The pharmacological effects of GS include the stimulation of proteoglycan synthesis by chondrocytes (anabolic effects), and the inhibition of cartilage degrading enzymes (catabolic effects). GS also possesses antiinflammatory activity through prostaglandin-independent mechanism. OA clinical trials have shown that long-term use of GS (1,500 mg/day) can delay the disease progression (changes in the joint space narrowing) and control OA signs and symptoms. GS is well tolerated and no severe adverse effects have been observed in GS treated patients. Therefore, GS may potentially be used in OA therapy as a specific drug to delay disease progression as well as to improve signs and symptoms of the disease.